Sikhism - Singh, Nikky-Guninder Kaur. (New York : Chelsea, 2009)
Describes the basic tenets of Sikhism, tells the story of its growth in India, examines the recent move toward greater political independence within the Indian nation, the effects of Hindu nationalism on the Sikh community, and issues of cultural adaptation, persecution, and and subsequent education now taking place in the West.
Introduction: Sikhism and the modern world -- Guru Nanak and the origins of the Sikh faith -- Sikh tradition and the Guru Granth -- Sikh thought -- Sikh ethics -- Religious life and rites of passage -- Sacred space and altered time -- Women and Sikhism -- Siky tradition and modern culture.
Includes bibliographical references and index.
Keywords: Sikhism -- Juvenile literature; Sikhism